Respect for Trademarks teaching materials, teachers' notes (WIPO, 2019)
"Aimed at students aged 14+, this resource offers a range of activities to support your teaching about the importance of protecting intellectual property (IP) rights worldwide. The focus of the resource is on trademarks and their role in protecting the rights of consumers and producers of goods and services. Throughout the resource, learning activities are enriched with interviews with experts in the field of intellectual property rights and branding. The resource is informed throughout by the concept of balance between the interests of the owners of rights and of consumers. It seeks to stimulate reflection as to the right way in which building respect for IP rights as a tool for development can deliver benefits both for right owners and for the economy and society as a whole" -- Introduction, "Dirigido a estudiantes mayores de 14 años, este recurso ofrece una variedad de actividades para apoyar su enseñanza sobre la importancia de proteger los derechos de propiedad intelectual (PI) en todo el mundo. El enfoque del recurso es sobre las marcas registradas y su papel en la protección de los derechos de los consumidores y productores de bienes y servicios. A lo largo del recurso, las actividades de aprendizaje se enriquecen con entrevistas a expertos en el campo de los derechos de propiedad intelectual y la marca. El recurso se basa en el concepto de equilibrio entre los intereses de los propietarios de los derechos y los de los consumidores. Pretende estimular la reflexión sobre la forma correcta en que fomentar el respeto por los derechos de PI como herramienta para el desarrollo puede generar beneficios tanto para los titulares de los derechos como para la economía y la sociedad en su conjunto" -- Introducción,